2004
DOI: 10.1007/s10334-003-0030-8
|View full text |Cite
|
Sign up to set email alerts
|

Automatic segmentation and plaque characterization in atherosclerotic carotid artery MR images

Abstract: In vivo MRI provides a means to non-invasively image and assess the morphological features of atherosclerotic carotid arteries. To assess quantitatively the degree of vulnerability and the type of plaque, the contours of the lumen, outer boundary of the vessel wall and plaque components, need to be traced. Currently this is done manually, which is time-consuming and sensitive to inter- and intra-observer variability. The goal of this work was to develop an automated contour detection technique for tracing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
113
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(116 citation statements)
references
References 19 publications
2
113
1
Order By: Relevance
“…In many pathologies, a limited number of quantitative parameters describe the relevant clinical findings from the imaging study. Like any image processing system, automated segmentation algorithms can produce mistakes, e.g., when the contrast level or the amount of noise differs from those specified or when the bifurcations or closely located vessels are misinterpreted by the algorithm and as such affect the segmentation result (Adame et al 2004). To obtain correct measurements, manual adjustments or overwrites to automated segmentation results are frequently needed in routine clinical practice.…”
Section: A Multimodal Visualization Framework For Medical Image Analysismentioning
confidence: 99%
“…In many pathologies, a limited number of quantitative parameters describe the relevant clinical findings from the imaging study. Like any image processing system, automated segmentation algorithms can produce mistakes, e.g., when the contrast level or the amount of noise differs from those specified or when the bifurcations or closely located vessels are misinterpreted by the algorithm and as such affect the segmentation result (Adame et al 2004). To obtain correct measurements, manual adjustments or overwrites to automated segmentation results are frequently needed in routine clinical practice.…”
Section: A Multimodal Visualization Framework For Medical Image Analysismentioning
confidence: 99%
“…We analyzed all of the images using the VesselMASS software package developed at our institution (23). This software package allows the semiautomated detection of the luminal and outer wall boundaries of the vessel wall from MR images, and the subsequent derivation of various quantitative parameters describing the vessel wall.…”
Section: Image Analysismentioning
confidence: 99%
“…Combinations of such techniques are beginning to automatically yield the desired in vivo characterizations of plaque tissue. For example, Adame et al recently showed the potential to automatically characterize the fibrous cap based on segmentation of contrast-enhanced images (97).…”
Section: Quantitative Analysis Techniques Image Processing Techniquesmentioning
confidence: 99%